Proceedings of the Society of British Neurological Surgeons (1969)
The 79th Meeting of the Society of British Neurological Surgeons was held at the London Hospital on 30 and 31 May 1969. The President, Mr. John O'Connell (London), was in the Chair. During the course of the meeting, the fifth Sir Hugh Cairns Memorial Lecture, entitled `The Place of Microsurgical Techniques in Neurological Surgery', was delivered by Professor Hugo Krayenbühl (Zürich).